Sampling and preparation of c.200 mm diameter cylindrical rock samples for geomechanical experiments. (April 2020) - Fraser-Harris, A.; Lightbody, A.; Edlmann, K.; Elphick, S.; Couples, G.D.; Sauter, M.; McDermott, C.I.
Abstract: Experimental investigation of rock mechanical properties of real and artificial samples often requires much care and attention to detail during sample preparation. This especially applies to high fidelity state of the art complex experimental apparatuses where sample tolerance is low due to the complexity of the measuring and stress control devices as well as the nature of the experiments to be conducted. Although sometimes mundane, the sample preparation methodology is as equally important as the experimental apparatus itself, and can require several new technological developments. The methodology and technical developments required to prepare realistic heterogeneous, fractured and natural reservoir analogue rock samples for coupled thermo-hydro-mechanical-chemical process experimental investigation is described here. We present the sample recovery and preparation procedures for large ( c. 200 mm diameter), cylindrical samples of 200 mm ± 5 mm length, with variable composition and mechanical properties e.g. rock strength, existing fractures/fracture networks, macro-porosity, or lithic fragments. Although the technology demonstrated is for a specific application, the procedures developed, equipment and methodology are applicable to multiple sizes of sample requirements. Highlights: Large ( c. 200 mm diameter) synthetic rock-analogue sample construction and rock sample collection techniques described. New sample preparation apparatuses described for large natural rock samples. Step-by-step sample preparation methodology presented.